The Blake mysteries [videorecording (DVD)] : ghost stories - Garner, Nadine; McClory, Belinda, 1968-; Tobeck, Joel, 1971- (ITV Studios Global Entertainment, 2019)
It's 1963. JFK has been assassinated. The world has changed... and tremors are being felt even all the way in Ballarat. Jean Blake is still adjusting to life after her husband Lucien's disappearance eight months earlier, when she's unexpectedly drawn into the investigation of a pair of bizarre murders. Both cases seem linked to a series of newspaper articles recently published in The Courier and Ballarat's most infamous unsolved mysteries. No one knows the town's history better than Jean and she's determined to help, despite push-back from Chief Superintendent Matthew Lawson.